Global responsibility vs. individual dreams: addressing ethical dilemmas created by the migration of healthcare practitioners. Issue 1 (1st January 2020) - Hossain, Fahmida
ABSTRACT: Background The migration of health care professionals from developing to developed countries is a trend. This migration benefits the destination countries but is quite often devastating to healthcare systems within the home countries. Skilled practitioners from developing countries forego opportunities in their homelands to migrate to developed countries. This leaves a vacuum of talent, weakening the health systems in the 'home' countries. Methods This piece analyzes the consequence of such migration through the lens of the four principles of Universal Declaration of Bioethics and Human rights (UDBHR): equality, justice and equity, solidarity and cooperation, and sharing of benefits. Results In the light of moral imagination and moral reflection, we can understand one another as global citizens. Policymakers must develop guides to restore balance and ensure equitable healthcare worldwide. Incorporating ethics education in medical schools and hospitals, implementing temporary migration visas, and helping home countries offer attractive compensation can address this concern. Conclusions Health is a universal human right; the well-being of all must be addressed without overly limiting the rights of practitioners to build the lives they imagine. On the other hand, practitioners should consider themselves global citizens and consider their ethical obligations when considering their migration.